Socio-Economic Characteristics, Income, and Feasibility Analysis of Cabbage Farming in Sudajaya Girang Village, Selabintana District, Sukabumi Regency - Nurul Annisa Syam; Endang Tri Astutiningsih; Neneng Kartika Rini (Tarjih : Agribusiness Development Journal, 2026)
This study analyzes the socio-economic characteristics of cabbage farmer households in Sudajaya Girang Village, Selabintana District, Sukabumi Regency. A quantitative descriptive approach was employed using purposive sampling to select 30 cabbage farmers as respondents. The study utilized both primary and secondary data. Descriptive analysis was conducted to examine farmers’ socio-economic characteristics, while farm performance was assessed through cost, revenue, income, and Income Cost Ratio (R/C Ratio) analyses. The results indicate that most farmers (53.33%) were of productive age, while the majority had a low level of formal education, with 56.67% completing only elementary school. Farmers generally possessed considerable farming experience and had a moderate number of family dependents. The average landholding size was 0.18 hectares, and most respondents (63.33%) cultivated their own land. These characteristics reflect the dominance of small-scale family farming in the study area. Economically, cabbage farming generated an average net income of IDR 12,564,017 per planting season, equivalent to IDR 66,533,996 per hectare. The calculated R/C ratio of 4.95 demonstrates that cabbage farming is highly profitable and financially feasible. This means that every IDR 1.00 spent on production costs generated IDR 4.95 in revenue. Income from cabbage cultivation also contributed substantially to overall household earnings. The findings suggest that socio-economic characteristics, land ownership, and farm resources play important roles in determining farm performance and household welfare. Therefore, policies that improve farmers’ access to production inputs, strengthen agricultural extension services, and enhance farm management skills are essential to maintain profitability and improve the economic resilience of cabbage farming households.